Awaken the Giant Within : How to Take Immediate Control of Your Mental, Emotional, Physical and Financial Destiny - Robbins, Anthony (Rawalpindi Services Book Club, 2014)
Author shows how to take immediate control of mental, emotional, physical, and financial destiny with strategies from his Date with Destiny seminar.
Include Illustrations and Index
Keywords: Success -- Self-Actualization (Psychology) -- Control (Psychology)